The 4th global coral bleaching event: ushering in an era of near-annual bleaching - Blake L. Spady; William J. Skirving; Jacqueline L. De La Cour; Erick F. Geiger; Gang Liu; Ove Hoegh-Guldberg; Andrew Norrie; Scott F. Heron; Morgan W. Pomeroy; Graham Kolodziej; Kristen T. Brown; Derek P. Manzello (Coral Reefs, 2026)
Increasingly frequent marine heatwaves have escalated the prevalence and extent of mass coral bleaching events. Global-scale coral bleaching events (GCBEs) can unfold when marine heatwaves impact reefs across all tropical ocean basins within a common period. Here, we define an objective, quantifiable index to compare periods of satellite-derived coral heat stress accumulation globally from 1985 to 2025 and examine their relationship to confirmed GCBEs. We uncover an uninterrupted and ongoing period of global coral heat stress from 2018 to 2025, affecting an unprecedented 87% of reef areas globally. The average intensity has also been record-setting, with the median global heat stress accumulation on reef areas nearly 50% greater than the previous GCBE record. This has largely been driven by general ocean warming, as recent baseline global surface ocean temperatures (2019–2023) are comparable to extreme anomalous conditions observed ~ 25 years ago. The development of a strong El Niño event in 2023, superimposed upon the already anomalously warm ocean, culminated in the 4th GCBE, the most extensive and intensive on record. Qualitative observations of coral bleaching have been reported from 84 countries spanning all coral-containing ocean basins. An analysis of the extent and magnitude of heat stress suggests that bleaching may have impacted 98 of the 102 countries with coral reefs. GCBE4 (2023–present) marks a period of heat stress that is unprecedented by every investigated metric. However, global-scale coral bleaching-level heat stress has persisted for almost the entirety of the last decade, bringing many reef areas into an era of near-annual bleaching.

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Trends in bird species richness, abundance and biomass along a tropical urbanization gradient - Dan Chamberlain; Micheal Kibuule; Roger Skeen; Derek Pomeroy (Urban Ecosystems, 2017)

Retraction Note: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2014)

RETRACTED ARTICLE: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2013)

A Nationwide Assessment of the Biodiversity Value of Uganda's Important Bird Areas Network - HERBERT TUSHABE; JAMES KALEMA; ACHILLES BYARUHANGA; JOSEPHINE ASASIRA; PAUL SSEGAWA; ANDREW BALMFORD; TIM DAVENPORT; JON FJELDSÅ; IB FRIIS; DEBORAH PAIN; DEREK POMEROY; PAUL WILLIAMS; et al. (Conservation Biology, 2006)
BirdLife International's Important Bird Areas (IBA) program is the most developed global system for identifying sites of conservation priority. There have been few assessments, however, of the conservation value of IBAs for nonavian taxa. We combined past data with extensive new survey results for Uganda's IBAs in the most comprehensive assessment to date of the wider biodiversity value of a tropical country's IBA network. The combined data set included more than 35,000 site × species records for birds, butterflies, and woody plants at 86 Ugandan sites (23,400 km 2 ), including 29 of the country's 30 IBAs, with data on additional taxa for many sites. Uganda's IBAs contained at least 70% of the country's butterfly and woody plant species, 86% of its dragonflies and 97% of its birds. They also included 21 of Uganda's 22 major vegetation types. For butterflies, dragonflies, and some families of plants assessed, species of high conservation concern were well represented (less so for the latter). The IBAs successfully represented wider biodiversity largely because many have distinctive avifaunas and, as shown by high cross‐taxon congruence in complementarity, such sites tended to be distinctive for other groups too. Cross‐taxon congruence in overall species richness was weaker and mainly associated with differences in site size. When compared with alternative sets of sites selected using complementarity‐based, area‐based, or random site‐selection algorithms, the IBA network was efficient in terms of the number of sites required to represent species but inefficient in terms of total area. This was mainly because IBA selection considers factors other than area, however, which probably improves both the cost‐effectiveness of the network and the persistence of represented species.

Biology of the Springtails—Insecta: Collembola - Derek Pomeroy (International Journal of Tropical Insect Science, 1997)